2018
DOI: 10.1002/pat.4323
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of microencapsulated LDHs with melamine‐formaldehyde resin and its flame retardant application in epoxy resin

Abstract: Layered double hydroxides (LDHs) are emerging as a new and green high‐efficient flame retardant. But LDHs aggregate seriously because of their hydrophilicity, which affect deeply the mechanical and flame retardant properties of their composites. For the first time in this paper, microencapsulated LDHs (MCLDHs) with melamine‐formaldehyde (MF) resin were prepared by microencapsulation technology to enhance their compatibility and dispersion within epoxy resin (EP). The mechanical and flame retardant performances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 62 publications
(113 reference statements)
0
22
0
Order By: Relevance
“…Compared with the FTIR spectra of M, that of HMP showed a new absorption at 2934 cm −1 , which was attributable to the –CH 2 stretching vibrations [22,23]. In addition, the new peak observed at 1338 cm −1 correspond to the C–N stretching of CH 2 –N [24]. Both of them indicated that the –NH 2 of the M reacted with formaldehyde to generate prepolymers.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the FTIR spectra of M, that of HMP showed a new absorption at 2934 cm −1 , which was attributable to the –CH 2 stretching vibrations [22,23]. In addition, the new peak observed at 1338 cm −1 correspond to the C–N stretching of CH 2 –N [24]. Both of them indicated that the –NH 2 of the M reacted with formaldehyde to generate prepolymers.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Wang et al prepared super hydrophobic Mg/Al‐LDH by gradual deposition of poly (dimethyl siloxane) (PDMS) and 1H, 1H, 2H, 2H‐perfluorododecyl trichlorosilane (FDTS), showing self‐cleaning characteristics and flame retardancy. It is worth mentioning that melamine formaldehyde (MF) resin microencapsulated LDHs was first prepared by microencapsulation technology and displayed good compatibility and dispersion in epoxy resin . However, these modifications only improve the compatibility of the LDH by surface or intercalation treatment, and the synergistic flame‐retardant effect on the polymer is inconspicuous.…”
Section: Introductionmentioning
confidence: 99%
“…The higher cross‐linking density and hydrogen bonding result in tighter chain packing. The tighter chain packing and the rigid structure of DHA‐B are good for increasing E′ …”
Section: Resultsmentioning
confidence: 99%